Philosophy in the mass age - Grant, George Parkin, 1918-1988 (University of Toronto Press, 1995)
When George Grant delivered Philosophy in the Mass Age over the CBC radio network early in 1958, it was an immediate hit. He criticized the Western notion of progress and affirmed the role of philosophy in teaching and assisting people in understanding. Robert Fulford described it then as stunningly effective: 'Grant's talks, obviously the product of a supple and curious mind, were models of their type - learned but clear, original but persuasive, highly personal but intensely communicative.'Grant's analysis of lhe paradox of modernity is no less intriguing today. The need to reconcile freedom with the moral law 'of which we do not take the measure, but by which we are measured and defined' is still an issue in our times. William Christian has restored the text of the original 1959 edition. He has supplemented it with material from the broadcast version of the lectures, including a ninth lecture, not previously published, in which Grant responded to listeners' questions. The controversial introduction to the 1966 edition appears as an appendix.